An unusual self-inflicted injury of the breast. Issue 592 (February 1975) - Sampson, D.
Abstract : A self-inflicted injury of the breast can present difficult diagnostic problems as is illustrated by the case report. A young woman had excoriated her left nipple causing profuse haemorrhage. Following excision of the nipple and a breast biopsy, the patient presented 1 month later with an abscess caused by the introduction of stones and gravel into the biopsy wound.